EVALUATION OF YIELD PERFORMANCE AND QUALITY PARAMETERS OF BREAD WHEAT CULTIVARS CULTIVATED IN RAINFED CENTRAL ANATOLIA - B. Aktas (Journal of Animal and Plant Sciences, 2022)
There are limited number of wheat cultivars recommended for successful cultivation under the rainfed conditions of the Central Anatolia.This research was conducted for determining grain yield potential and some quality traits of five commonly cultivated bread wheat cultivars (Bezostaja 1, Gerek 79, Bayraktar 2000, Tosunbey, and Sonmez 2001) cultivated over large areas in the Central Anatolia. The experiments were conducted using randomized complete block design with four replications during 2007-2015. The cultivars were evaluated in terms of mean grain yield, regression coefficient (bi), regression constant (a), coefficient of determination (R2) and coefficient of variation (CV) for their stability in 38 environments. In addition, stability of the cultivars was assessed on the graphs generated with the use of GGE (Genotype + genotype by environment interaction) biplot analysis. Genotype × environment interaction (GEI) was found significant (p<0.01). In the GGE-biplot analysis of the grain yields, 72.84% of the total variation was explained by PC1 and PC2. Mean grain yields of the genotypes varied between 4018.4-4826.4 kg ha-1, thousand-kernel weights varied between 30.0-35.6 g, test weights between 76.5-79.1 kg, protein contents between 13.4-15.3% and Zeleny sedimentation values between 34.2-46.7 ml. These detailed stability level of the studied cultivars will be helpful for their utilization in future breeding programs. Bayraktar 2000 and Sonmez 2001 had the highest grain yields, the bi values of greater than 1. Negative values indicated that these genotypes have potential to improve grain yields under appropriate environmental conditions. Bezostaja 1 was identified as the most prominent genotype for quality traits. The results of this study emphasize importance of selecting genetically stable wheat genotypes in breeding programs.
Keywords: Triticum aestivum L.; cultivar development; grain yield and quality; stability; GGE-biplot; rainfed agriculture